Review of The Effect of Neodymium and Ytterbium on Microstructure and Mechanical Properties of Magnesium Alloy - Roslan, Nazatul Nazuhah; Ahmad, Rosli (Research Progress in Mechanical and Manufacturing Engineering, 2022)
The impact of the rare earth elements neodymium (Nd) and ytterbium (Yb) on the microstructure and mechanical characteristics of the magnesium alloy was examined in this study. By referring to past research and journal papers, the case study method is used. The studies were carried out using optical microscopy (OM) and scanning electron microscopy (SEM) with electron dispersive spectroscopy (EDS) in the references, which revealed that neodymium and ytterbium changed the grain size of the alloys. Optical microscopy revealed the grain size of the alloys, indicating grain refinement. According to SEM/EDS measurements, the addition of Nd and Yb caused a new development of intermetallic phases at grain boundaries, which dissolved into the magnesium matrix, according to SEM/EDS measurements. Both additions increased the Mg-Zn-Zr base alloys’ ultimate tensile strength (UTS) and hardness value.